Percy Jackson's Greek heroes - Riordan, Rick (Disney-Hyperion, 2015)
"Who cut off Medusa's head? Who was raised by a she-bear? Who tamed Pegasus? It takes a demigod to know, and Percy Jackson can fill you in on the all the daring deeds of Perseus, Atalanta, Bellerophon, and the rest of the major Greek heroes. Told in the funny, irreverent style readers have come to expect from Percy -- Provided by publisher.